Study of the Economic Potential of the Innovative Development of Hotel Enterprises in Azerbaijan - Rza-zadeh Nuray Rauf (Економічний вісник Донбасу, 2019)
Innovation implementation is a very important and necessary element in improving company competitiveness. Globalization processes, the emergence of new market demands and opportunities to meet these needs force hotel companies to move on to the path of creative growth.
Our study aims at a comprehensive review of the economic potential of Azerbaijan's creative hotel business growth. This is necessary to identify promising areas and select the best creative approaches for the growth of these enterprises. Those approaches will suit those hotel companies ' capabilities.
In line with this aim, the article discusses the structural components of hotels ' innovative potential, including a framework for evaluating hotels in Baku's innovative potential. We are talking about the element intellectual, science, academic, manufacturing and technological, economic, marketing, organizational and managerial. Moreover, the researchers suggested a framework for a systematic analysis of hotel businesses ' creative capacity. It is focused on the use of a system of qualitative and quantitative measures that describe both the state of its individual structural components and the overall level of integration of hotel enterprises ' creative potential.
Empirical research approaches-comparison, evaluation, grouping, as well as logical generalization, statistical analysis, and a systematic approach – were used when writing the article.
The application of economic-mathematical and economic-statistical methods allowed an unbiased quantitative analysis of hotels' creative potential, identified patterns in the growth of their structural components, identified imbalances and contradictions, and predicted their further development.
The study succeeds in finding existing problems in some of the constituent elements of hotel businesses' creative capacity in Baku. The outcome is also a series of steps to aggressively harness the economic potential of hotels' creative growth. Впровадження інноваційних технологій – істотно важливий і необхідний чинник підвищення конкурентоспроможності компаній. Процеси глобалізації, виникнення нових потреб ринку і можливостей їх задоволення змушує переходити на шлях інноваційного розвитку і готельні підприємства.
Метою даного дослідження є комплексний розгляд економічного потенціалу інноваційного розвитку готельних підприємств Азербайджану, для визначення перспективних напрямків розвитку даних підприємств і вибору оптимальних інноваційних стратегій, що відповідають можливостям даних готельних підприємств, що забезпечують їх успішний інноваційний розвиток.
Відповідно до поставленої мети, у статті розглянуто структурні компоненти інноваційного потенціалу готелів, дана система узагальнюючих показників оцін¬ки інноваційного потенціалу готелів м. Баку, а саме таких її складових, як: інтелектуальна, наукова, науково-дослідницька, виробничо-технічна, фінансова, маркетингова і організаційно-управлінська; запропонована авторська методика комплексної оцінки інноваційного потенціалу готельних підприємств, заснована на використанні системи якісних і кількісних показників, що характеризують, як стан його окремих структурних компонентів, так і загальний інтеграційний рівень інноваційного потенціалу готельних підприємств.
При написанні статті використовувалися методи емпіричного дослідження: порівняння, спостереження, угрупувань і такі загальнологічні методи, як логічне узагальнення, статистичний аналіз і системний підхід.
Застосування економіко-математичних і економіко-статистичних методів дозволило дати об'єктивну кількісну оцінку інноваційного потенціалу готелів, визначити тенденції розвитку його структурних компонентів, виявити існуючі в них диспропорції і протиріччя, прогнозувати їх подальший розвиток.
Результатом дослідження є виявлення існуючих проблем у ряді складових інноваційних потенціалів готельних підприємств м. Баку, а також розробка комплексу заходів щодо активізації використання економічного потенціалу інноваційного розвитку аналізованих готелів. Внедрение инноваций – существенно важный и необходимый фактор повышения конкурентоспособности компаний. Процессы глобализации, возникновение новых потребностей рынка и возможностей их удовлетворения заставляет переходить на путь инновационного развития и гостиничные предприятия.
Целью данного исследования является комплексное рассмотрение экономического потенциала инновационного развития гостиничных предприятий Азербайджана, для определения перспективных направлений развития данных предприятий и выбора оптимальных инновационных стратегий, соответствующих возможностям данных гостиничных предприятий, обеспечивающих их успешное инновационное развитие.
В соответствии с поставленной целью, в статье рассмотрены структурные компоненты инновационного потенциала гостиниц, дана система обобщающих показателей оценки инновационного потенциала отелей г. Баку, а именно таких ее составляющих, как: интеллектуальная, научная, научно-исследовательская, производственно-техническая, финансовая, маркетинговая и организационно-управленческая; предложена авторская методика комплексной оценки инновационного потенциала гостиничных предприятий, основанная на использовании системы качественных и количественных показателей, характеризующих, как состояние его отдельных структурных компонентов, так и общий интеграционный уровень инновационного потенциала гостиничных предприятий.
При написании статьи использовались методы эмпирического исследования: сравнения, наблюдения, группировок и такие общелогические методы, как логическое обобщение, статистический анализ и системный подход.
Применение экономико-математических и экономико-статистических методов позволило дать объективную количественную оценку инновационному потенциалу гостиниц, определить тенденции развития его структурных компонентов, выявить существующие в них диспропорции и противоречия, прогнозировать их дальнейшее развитие.
Результатом исследования является выявление существующих проблем в ряде составляющих инновационных потенциалов гостиничных предприятий г. Баку, а также разработка комплекса мероприятий по активизации использования экономического потенциала инновационного развития анализируемых гостиниц.